Performance of a low-cost septic tank system with integrated microbial support system and a tertiary level treatment without aeration - Macapinlac, Emma Alcaraz (College of Engineering, University of the Philippines Diliman, 2014)
Majority of the septic tanks installed in the Philippines were not properly designed (open at the bottom) or leaking (walls porous or not watertight, which contaminate the ground water. Depending on the design, the BOD removal varies from 40 to 70%. This study presented a low-cost septic tank, the effluent of which passed DENR standards. The septic tank consisted of four 200-liter plastic drums (containers discarded by Industry) consecutively joined together followed by a 500 liter filter reactor, which provided extra capacity. During the start-up (eight weeks) the system showed a COD removal of 35-56%. A microbial support system consisting of pyrolyzed coconut shell in porous containers or screen was placed in the tanks and the reactor (except in the first tank, which is for settling). A microbial culture powder supplied by Dr. Leo Padua resulted In 42-65% COD removal. Next, a liquid culture supplied by Mr Edgar Maranan resulted in 41-60% COD removal. Finally, a culture supplied by Mr George Whang gave a 75-79% COD removal. For nutrient removal, aquatic plants and algae were used, which both grew depending on the COD level of the effluent wastewater. The maximum nitrogen removal was 92% while for phosphorous, 67%. COD and color were also reduced. The algae production was 0.4-0.9 g algae/day using 3 liters of liquid per day. The effluent was treated by electrocoagulation using aluminum electrodes operated at 10 volts DC and a current density of 87.8 amperes/sq meter. The final COD was 48 ppm and the BOD was 32 ppm, which passed the DENR effluent standards for discharge into Class C waters. The coliform count was 1.7 x 103 MPN/100ml., which also passed the standard limit of 1 x 104 MPM/100 ml.